International Cybersecurity on Railway Transport: Methodological Approaches and Normal Procedural Framework - S. E. Adadurov; S. V. Diasamidze; A. A. Kornienko; A. A. Sidak (Вестник Научно-исследовательского института железнодорожного транспорта)
The paper deals with methodological approaches and practical venues of international cooperation in the areas of information security and cybersecurity on railway transport. The approaches were adopted by the workshop “Cybersecurity on Railway Transport” established within the framework of the COLOPOFER program. There are analyzed main factors and prerequisites governing the necessity of hacking countermeasures on the part of railway IT infrastructure. Also discussed are cybersecurity related definitions. There are presented principal provisions of normative techniques being developed by the international workshop “Cybersecurity on Railway Transport”. Basic IT information infrastructure objects of railway transport are characterized with respect to their hacking susceptibility and their most vulnerable components are highlighted. There is presented classification of the types of computer attacks and their implementation me-dia. Also discussed are organizational and routine hacking countermeasures to be taken in the railway IT infrastructure environment.